Vegetative propagation of Bagoadlau (Xanthosthemon philippinensis Merr.) using indolebutyric acid - Romano, Romel S.; Vallesteros, Shierel F.; Pascua , Romnick L. (Brawijaya University, 2024)
The research investigated the vegetative propagation of Bagoadlau (Xanthosthemon philippinensis Merr.) stem cuttings using different concentrations of indolebutyric acid (IBA). Pretreated cuttings were planted in polyethylene bags and observed in a fully covered chamber for 45 days. The study employed a single trial of completely randomized design (CRD) with five treatments (500 ppm, 100 ppm, 1,500 ppm, and 2000 ppm), each replicated four times. Results indicated significant variations among treatment means in terms of percent shooting, shoot length, percent rooting, number and length of adventitious roots, and percent callusing. Notably, 500 ppm and 1,500 ppm demonstrated the highest outcomes in percent shooting, shoot length, percent survival, measurement of adventitious roots, count of roots, and percentage of rooting. In contrast, the survival percentage of T2 (500 ppm) displayed the highest rate and consistent performance compared to other treatments. Hence, the study recommends using 500 ppm and 1,500 ppm for effective rooting of Bagoadlau (Xanthosthemon philippinensis Merr.) stem cuttings. The successful propagation of native species like Bagoadlau is particularly relevant to ecosystem restoration efforts in regions marked by land degradation and mining activities. The study addresses several crucial aspects by successfully establishing Bagoadlau on such lands. This includes the restoration of native biodiversity, improved soil, and water quality through stabilizing soil, preventing erosion, and acting as a natural filtration system.